Proceedings of the Halfway to the Future Symposium 2019 2019
DOI: 10.1145/3363384.3363389
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Communal Technology Use in the Home

Abstract: Device use in smart homes is becoming increasingly communal, requiring cohabitants to navigate a complex social and technological context. In this paper, we report findings from an exploratory survey grounded in our prior work on communal technology use in the home [4]. The findings highlight the importance of considering qualities of social relationships and technology in understanding expectations and intentions of communal technology use. We propose a design perspective of social expectations, and we sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Apthorpe et al [2] found, via a study involving 13 interviews and a survey of 508 individuals, that the lack of nuanced sharing solutions for home IoT devices meant that households were required to fall back to "social resolution techniques", such as agreeing not use particular features, in order that ongoing use remains acceptable for all involved. Agreement and discussion from all participants about the goals and requirements of a device is a fundamental part of what Kraemer et al [35] refer to as "group efficacy", a key element of acceptable multi-user device management. However, power dynamics need to be recognized as a limiting factor in group efficacy: Bernd et al [4] report that nannies working within a family context did not consider themselves to have enough power in the relationship with parents -their employers -to ask for smart surveillance systems to be switched off.…”
Section: Multi-use Of Iot Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apthorpe et al [2] found, via a study involving 13 interviews and a survey of 508 individuals, that the lack of nuanced sharing solutions for home IoT devices meant that households were required to fall back to "social resolution techniques", such as agreeing not use particular features, in order that ongoing use remains acceptable for all involved. Agreement and discussion from all participants about the goals and requirements of a device is a fundamental part of what Kraemer et al [35] refer to as "group efficacy", a key element of acceptable multi-user device management. However, power dynamics need to be recognized as a limiting factor in group efficacy: Bernd et al [4] report that nannies working within a family context did not consider themselves to have enough power in the relationship with parents -their employers -to ask for smart surveillance systems to be switched off.…”
Section: Multi-use Of Iot Devicesmentioning
confidence: 99%
“…Recently, research has focused upon the various usability and privacy issues of the multi-use of home IoT devices [4,11,24,35,72]. 1 The privacy of all people living within a home is of key importance when considering home IoT devices, and keeping data that is intended to be private out of the public domain is fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…Use of smart assistants depends on spatial and temporal factors, such as where the device is located and when in the day it is used [17]. Research into the social context of smart home devices notes a reliance on existing work or social relationships to determine who manages the technologies [15], adding that the amount of control given to a user is often determined by technical ability and device familiarity. Primary or more knowledgeable users may accommodate less technically capable users and guest users.…”
Section: B Shared Use and Managementmentioning
confidence: 99%
“…Within a smart home, where consumer Internet-of-Things (IoT) devices are used, these smart assistants learn on increasing amounts of data to become more useful ( [15], [17], [21], [32], [37]). Smart assistants such as the Amazon Echo can gather audio data, location data, log queries, and access linked third-party apps [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation